2002
DOI: 10.1002/1439-7633(20020603)3:6<526::aid-cbic526>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The Ternary Complex of Cytochrome f and Cytochrome c: Identification of a Second Binding Site and Competition for Plastocyanin Binding

Abstract: The complex of yeast cytochrome c and cytochrome f from the cyanobacterium Phormidium laminosum was investigated by NMR spectroscopy. Chemical shift perturbation analysis reveals that residues around the haem edge of cytochrome c are involved in the complex interface. Binding curves derived from an NMR spectroscopy titration at 10 mM ionic strength indicate that there are two sites for cytochrome c with binding constants of approximately 2 x 10(4) M(-1) and 4 x 10(3) M(-1). A protein docking simulation with NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…Interestingly, in a quite recent study, two binding site for cytochrome c were identified on cytochrome f, involved in formation of a non-physiological complex [25].…”
Section: Nmr Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in a quite recent study, two binding site for cytochrome c were identified on cytochrome f, involved in formation of a non-physiological complex [25].…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…In this respect, it is also worth noting that the interface regions on cytochrome c in the Salemme model and in the electrostatically dominant model are adjacent. The importance of inter-protein dynamics in electron transfer complexes appears to be quite different in different systems [14,24,25], but likely plays a crucial role in modulating the rate of the process [68].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). It can be concluded that the binding affinity of cytf for Ana-cytc 6 is ϳ10 4 M Ϫ1 , which is about 2 orders of magnitude greater than the affinity for the physiological partner, P. laminosum Pc (15,29). From the ratio of the observed ⌬␦ Bind to the fitted ⌬␦ Max (Fig.…”
mentioning
confidence: 96%
“…The different roles of electrostatics and hydrophobics can be further illustrated by comparison with the recently characterized, non-physiological complex of yeast cytochrome c (cytc) and cytf (29). It was found that cytf binds two equivalents of cytc with binding constants of ϳ2 ϫ 10 4 M Ϫ1 and 4 ϫ 10 3 M Ϫ1 .…”
mentioning
confidence: 99%